The Subdistrict Government’s Strategy for Accelerating the Establishment of the Merah Putih Cooperative in Koto Tangah Subdistrict, Padang City - Rahmazari, Suci; Malau, Hasbullah (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although cooperatives as instruments of people-centered economics have received increasing scholarly attention, research specifically examining sub-district government strategies for accelerating the implementation of the Merah Putih Cooperative remains limited. This study aims to analyze the strategies of the sub-district government in accelerating the implementation of the Merah Putih Cooperative in Balai Gadang Sub-district, Padang City, based on Presidential Instruction No. 9 of 2025. A qualitative approach with a descriptive method was employed. Informants were selected using purposive and snowball sampling techniques, while data were collected through interviews, observations, and documentation. The data were analyzed using the Miles and Huberman interactive model. The findings indicate that the strategies implemented were relatively effective and progressive, as reflected in strategy formulation based on local potential and implementation through the development of business units, including honeybee production (galo-galo), the provision of basic necessities, and the empowerment of micro, small, and medium enterprises (MSMEs). However, implementation still faces challenges related to regulatory dynamics, capital constraints, and the absence of a measurable performance system. This study concludes that sub-district government strategies play a crucial role in accelerating cooperative implementation. The study contributes to policy implementation and local economic development literature by highlighting the importance of locally grounded strategies, strengthened performance systems, and policy support to ensure the sustainability of the Merah Putih Cooperative program.